The Hybridization of Distance Learning in Brazil – An Approach Imposed by Culture - Litto, Fredric Michael (International Review of Research in Open and Distributed Learning, 2002)
Institutions of higher education in Brazil are seriously behind in their development of approaches which make use of distance education techniques, in part due to widespread lack of credibility of these approaches both inside and outside academic communities, but even more so because of the highly centralized control over all aspects of higher education on the part of the country’s Ministry of Education. Despite the country’s capacity and need to do so, the rigid and pedagogically conservative attitude of this Ministry over the last three decades, combined with the equally intransigent and politically-motivated decisions of the National Congress, have discouraged practically all attempts by educational institutions, public and private, to invest significantly in the development of innovative and far-reaching initiatives employing distance learning methods. Hybridization, or the combination, in the same course, of face-to-face situations for learning with those carried out using distance learning techniques, represents in Brazil is not an option motivated by pedagogical choice, but rather the only avenue legally permitted in the field of formal, degree-granting higher education.